Autotransplantation of parathyroid grafts into the tibialis anterior muscle after parathyroidectomy: a novel autotransplantation site - Anamaterou, Chrysanthi; Lang, Matthias; Schimmack, Simon; Rudofsky, Gottfried; Büchler, Markus W.; Schmitz-Winnenthal, Friedrich Hubertus (BMC surgery, 2015)
Surgical management of renal secondary hyperparathyroidism (sHPT) is varying. Total parathyroidectomy with heterotopic autotransplantation (TPTX + AT) is one of the standard surgical procedures in sHPT, but there is no consensus about the optimal site for graft insertion. At the surgical department of the University Hospital of Heidelberg we prefer the autotransplantation into the tibialis anterior muscle. The aim of this study was to assess the long-term function of the auto-transplanted parathyroid tissue in this type of surgical procedure.
Gesehen am 23.07.2020